"It's just the luck of the draw": Luck, good farming and the management of animal disease in Aotearoa New Zealand. Issue 119 (February 2021) - Enticott, Gareth; Gates, M. Carolyn; Hidano, Arata
Highlights: Perceptions of luck influence farmers' behavioural responses to animal disease. Farmers do not associate animal disease control metrics with 'good farming' Discourses of good and bad luck helps farmers explain why some have animal disease. Discourses of luck reflect neoliberal practices of animal disease management. Luck justifies modern agricultural practices despite their disease risks. Abstract: The mobility of livestock in modern farming systems is connected with the geographical spread of animal disease. Government attempts to control this geography increasingly rely on practices of self-government that create new farming subjectivities to shape farming conduct. However, studies show that perceptions of luck are influential in shaping behaviour to environmental hazards, as are socio-cultural concepts of 'good farming' in which forms of cultural capital define appropriate conduct. This paper examines how luck is woven into farmers' understandings of disease and the conduct of 'good farming' in relation to government attempts to restrict the movement of cattle. Drawing on 41 qualitative interviews with farmers in Aotearoa New Zealand, the paper examines understandings of good farming in relation to a metrological system to encourage fewer high-risk livestock movements. Data reveal that luck is an important resource in shaping farmers' perceptions of animal disease, justifying their disease control behaviour; responses to practices of self-government; and allowing farmers to displace blame and rely on experts to manage animal disease. A focus on luck also highlights a range of competing versions of good farming and the importance of context when assessing the symbols of good farming. The failure to inscribe multiple forms of good farming within practices of animal disease self-government and narrowly associate good farming with disease freedom means they lack cultural relevance. In conclusion the paper considers the importance of luck for the concept of good farming and government approaches to managing the geography of animal disease.